Rituximab in Steroid-dependent Nephrotic Syndrome (Iranian Journal of Kidney Diseases, 2013)
Treatment of steroid-dependent nephrotic syndrome, particularly in patients who have failed to respond to multiple immunosuppressive drugs, remains challenging. Rituximab represents a new off-label therapeutic option. Here, we report the use of rituximab in 7 children with steroid-dependent nephrotic syndrome with various histological backgrounds who failed to maintain remission with other immunosuppression regimens. All patients received rituximab infusion, 750 mg/m2 in 2 doses, 2 weeks apart, and the subsequent doses were adjusted by clinical response. In all patients, complete B-cell depletion was observed after the first course of rituximab. Follow-up for at least 12 months showed sustained remission in 6 children. We conclude that rituximab can reduce the risk of relapses, reduce the burden of immunosuppression, and at least, offer a better control of steroid-dependent nephrotic syndrome with minimal doses of immunosuppressive agents and steroids.